Strategies for Preserving Cultural Elements in Translating Wilde’s the Selfish Giant - Marshanda Marshanda; Najwa Rizki Amalia; Nisrina Farida Ramadhanti; Diar Mukti Asri; Raysha Ramadhani; Abdul Syahid (Journal of English Language and Education, 2026)
Translation plays an important role in bridging linguistic and cultural differences, especially in literary texts where meanings are closely connected to cultural symbols and values. However, previous studies have mainly focused on non-literary translation or the classification of translation strategies, leaving the preservation of deeper symbolic and cultural meanings in literary works underexplored. This study aims to analyze the translation strategies used in preserving culture-specific items (CSIs) in Oscar Wilde’s The Selfish Giant and its Indonesian translation Raksasa Egois translated by Clara Ng and published by Fiksi Lotus in 2013. A qualitative comparative text analysis was employed by comparing the source text and target text to identify CSIs and examine the translation strategies applied. The findings reveal that literal translation, cultural equivalence, and adaptation were the main strategies used, with literal translation being the most dominant, particularly in ecological elements such as seasons and natural phenomena. While literal translation effectively preserves lexical meaning, it is less successful in maintaining deeper symbolic and cultural meanings embedded in the literary text. In contrast, cultural equivalence proves to be more effective in preserving religious meanings, while adaptation improves readability but reduces cultural specificity. In conclusion, the effectiveness of translation strategies depends on the type and cultural embeddedness of CSIs.